Plastome Sequences Help to Resolve Deep-Level Relationships of Populus in the Family Salicaceae - Zong, Dan; Gan, Peihua; Zhou, Anpei; Zhang, Yao; Zou, Xinlian; Duan, Anan; Song, Yu; He, Chengzhong (Frontiers in Plant Science, 2019)
Populus, a core genus of Salicaceae, plays a significant ecological role as a source of pioneer species in boreal forests. However, interspecific hybridization and high levels of morphological variation among poplars have resulted in great difficulty in classifying species for systematic and comparative evolutionary studies. Here, we present phylogenetic analyses of 24 newly sequenced Populus plastomes and 36 plastomes from GenBank, which represent seven genera of Salicaceae, in combination with a matrix of eighteen morphological characters of 40 Populus taxa to reconstruct highly supported relationships of genus Populus. Relationships among the 60 taxa of Salicaceae strongly supported two monophyletic genera: Populus and Salix. Chosenia was nested within the genus Salix, and five clades within Populus were divided. Clade I included the three taxa P. euphratica, P. pruinosa, and P. ilicifolia. Clade II contained thirteen taxa [P. adenopoda, P. alba, P. bolleana, P. davidiana, P. hopeiensis, P. nigra, P. qiongdaoensis, P. rotundifolia, P. rotundifolia var. duclouxiana, P. tremula, P. tremula × alba, P. tomentosa, and P. tomentosa (NC)]. Clade III included the ten taxa P. haoana, P. kangdingensis, P. lasiocarpa, P. pseudoglauca, P. qamdoensis, P. schneideri, P. simonii, P. szechuanica, P. szechuanica var. tibetica, and P. yunnanensis. Clade IV included P. cathayana, P. gonggaensis, P. koreana, P. laurifolia, P. trinervis, P. wilsonii, and P. xiangchengensis. The last clade comprised P. angustifolia, P. balsamifera, P. deltoides, P. deltoides × nigra, P. fremontii, P. mexicana, and P. trichocarpa. This phylogeny is also supported by morphological traits, including bark smoothness, bud size, petiole shape, leaf inflorescence, male anther length and male anther tip.